Performance of Stunting Reduction Acceleration Team: An Explorative-Qualitative Study in Indonesia-Timor Leste Border Area - Nahak, Maria Paula Marla; Nitsae, Veronika (Kesmas, 2024)
Stunting is a complex issue influenced by multiple factors, including specific factors within and outside the health sector. Achieving a significant reduction in stunting needs the involvement of relevant local government offices in the Stunting Reduction Acceleration Team (SRAT). This study aimed to investigate SRAT performance in a specific context of accelerating stunting reduction in Malaka District. This qualitative study, with a phenomenological approach, was conducted in Malaka District, Indonesia, and Timor Leste Border Area from July to September 2023. This study revealed four major themes of SRAT performance to accelerate stunting reduction in Malaka District: activities to accelerate stunting reduction, challenges faced in implementing the programs, supporting factors for program implementation, and alternative activities initiated by the local government. This study showed that the many local government agencies responsible for specific and sensitive interventions have effectively fulfilled their mandatories and roles in accelerating the elimination of stunting in Malaka District. However, inadequate internal coordination within SRAT has led to a dearth of harmonization in its execution.